(untitled) (Linguostylistic Studies, 2021)
Exclamations are a special class of words that express emotionally-expressive reactions, evaluations, expressions of will, without naming them. Depending on the context, they can acquire different semantic and stylistic possibilities. The interactives used by the authors in the fictional texts are particularly significant. Firstly, their use testifies to the affinity of works with living colloquial speech, and secondly, the writer can provide exclamations with a special semantic content, introducing them into neutral contexts. The language of Lesia Ukrainka’s drama-fairy-tale “The Forest Song” is analyzed in the article and the semantic and stylistic features of exclamations in it are determined. The language analysis of the text showed that the exclamations in the lines of the characters are used quite often and appropriately. They emphasize the emotional state of the character, give it an evaluative characteristic, reflect the dialectal features of local dialects. The study has revealed that one of the most productive exclamations is the primary emotional exclamations “o”, “oh”, “oy”, which often add emotional colour to the whole line. The semantics of interactives that play a communicative-voluntary function is analyzed. A number of verb-exclamation forms have been recorded, the peculiarity of which is the reflection of instantaneous and short-term action. Attention is paid to the exclamations of language etiquette, exclamations-oath, and exclamations-curses. Fixed interjections are divided into nine subgroups: emotional-evaluative, affective, vocative, negative, reflexive, imperative (commanding, motivating, appealing), etiquette, exclamations-curses, exclamations-oath. The most productive exclamations are emotional-evaluative and imperative. Exclamations play an important role in the speech of literary characters, as they help the author to convey more deeply and fully the worries, emotions and character traits of a hero.